Including or excluding religion and worldviews in schools? Finnish teachers' and teacher students' perceptions - Niemi, Pia-Maria (Journal of beliefs and values, 2020)
How schools navigate between the demands presented by secularisation, and the increasing plurality of religious traditions has become a very topical issue in many European countries, including Finland, in recent decades. The question is both practical and philosophical by nature because the ways in which various beliefs and values are represented in school practices and teaching content profoundly concern the educational mission of the schools. However, despite the topicality of the issue, little attention has been given to teachers' perceptions on whether public schools should, or should not, provide space for various religions and worldviews to become visible within the school life, and how schools should respond in practice to the perceived needs. In order to gain new knowledge on the topic, this study investigated Finnish teachers' and university students' (N = 181) perceptions of the representations of religions and worldviews, based on the perspectives of inclusion and exclusion. The statistical analysis revealed three factors titled as Religiously responsive approach', Secularist approach' and Equal visibility approach'. According to the main findings, current and future educators show various degrees of inter-religious sensitivity but principally supported the equal visibility of various traditions, rather than favouring strongly inclusivist or exclusivist practices.